Properties of Cassava Starch based Bioplastic Reinforced by Nanoclay - Nanang Eko Wahyuningtiyas; Heru Suryanto (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
Synthetic Synthetic plastic is chemical materials which cause severe environmental problems. Incinerating plastic waste leads to release of hazardous gases, which is not good for humans. Bioplastic can help reduce the dependence on fossil fuels and petroleum, that bioplastic can solve the problem of synthetic plastic use. This research aims to define the properties of the cassava starch-based bioplastic reinforced by nanoclay. Methods were experimental with bioplastic component of cassava starch, glycerol as plasticizer and nanoclay as reinforcement. The bioplastic was analyzed using XRD, tensile test, moisture absorption, biodegradability, and compared with another bioplastic. The results show that the addition of nanoclay into bioplastic results increasing the tensile strength of bioplastic also increases from 5.2 MPa to 6.3 MPa. This research revealed that complete degradation of nanoclay reinforced bioplastic could be achieved on the 6th day.